A revisited study of the low-lying electronic states of HF molecule. (September 2021) - Liu, Yadong; Sun, Qixiang; Liu, Yahong; Xue, Jianlei; Li, Rui; Yan, Bing
Abstract: Hydrogen fluoride (HF) has served as a benchmark molecule for ab initio methods. Consequently, it has been extensively investigated in the past few decades. The energy ordering of the low-lying triplet electronic states has proven controversial in previous computational studies. In this work, the Gaussian basis of F and H atoms are calibrated by adding diffuse functions to the aug-cc-pV5Z valence basis sets. The electronic structure of HF molecule is studied by the multireference configuration interaction method plus Davidson correction method (MRCI+Q). The potential energy curves (PECs) of 19 electronic states are computed, and the spectroscopic constants of the bound states are determined. The low-lying triplet Rydberg electronic states 2 3 Σ + ( 3 Σ + R1 ), 2 3 Π ( 3 ΠR1 ) and 1 3 Δ ( 3 ΔR1 ) are characterized and compared with the previous computational results. The transition dipole moments (TDMs) and Franck-Condon factors (FCFs) between the electronic states are subsequently calculated. Finally, the spontaneous radiative lifetimes of four spin-allowed transitions are obtained. The results of this paper will improve the understanding on the electronic excited states of HF molecule, especially the electronic structure and spectra characteristics of the triplet excited states.